Mass Spectrometry Based Forest Tree Metabolomics - Rodrigues, Ana Margarida (2022)
"This thesis describes the application of mass spectrometry (MS)-based metabolomics approaches to study the metabolite responses of Pinus pinaster to pinewood nematode (PWN) infection. The PWN Bursaphelenchus xylophilus is the causal agent of the pine wilt disease (PWD), a serious pathology to conifer forests with devasting ecological and economic impact."